2015
DOI: 10.1021/acs.organomet.5b00405
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Neutral and Cationic Pathways in Nickel-Catalyzed Insertion of Benzaldehyde into a C–H Bond of Acetonitrile

Abstract: Nickel catalysts supported by diethylamine-or aza-crown ether-containing aminophosphinite (NCOP) pincer ligands catalyze the insertion of benzaldehyde into a C−H bond of acetonitrile. The catalytic activity of neutral (NCOP)Ni(O t Bu) and cationic [(NCOP)Ni(NCCH 3 )] + are starkly different. The neutral tert-butoxide precatalysts are active without any added base and give good yields of product after 24 h, while the cationic precatalysts require a base cocatalyst and still operate much more slowly (120 h in ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 44 publications
3
35
0
Order By: Relevance
“…Electric elds generated by internal dipoles have been increasingly cited in selective or increased reactivity for organic synthesis. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Kanan et al have demonstrated that the eld generated by ion pairing modies the regioselectivity of Au(I)-catalyzed hydroarylation of 3-substituted phenyl propargyl ethers. 31 Coote et al have also reported using pH switchable elds that rely on protonationdeprotonation to vary radical stability.…”
Section: Introductionmentioning
confidence: 99%
“…Electric elds generated by internal dipoles have been increasingly cited in selective or increased reactivity for organic synthesis. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Kanan et al have demonstrated that the eld generated by ion pairing modies the regioselectivity of Au(I)-catalyzed hydroarylation of 3-substituted phenyl propargyl ethers. 31 Coote et al have also reported using pH switchable elds that rely on protonationdeprotonation to vary radical stability.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly generation of CN − anion was achieved using various systems such as Cu, NaH . Formation of metal‐cyano complexes were also observed during the cyanation and cyanomethylation using ACN with the various metals such as Ni, Ir‐PNP pincer, [70 NiNCOP Pincer, Cu, Cu/Ag and Ag . Shen and coworkers demonstrated that in presence of copper and TEMPO in a reaction, both cyanide anion as well as cyanide radical formations are possible …”
Section: Reaction Solvents As Precursors For the Installation Of Key mentioning
confidence: 92%
“…Pincer complexes were also studied for the cyanomethylation. Smith and Miller (2016) explored the Nickel‐NCOP type pincer complex for the hydrocyanomethylation of benzaldehyde using ACN (Scheme ). Two pathways were proposed (neutral and cationic) under present conditions.…”
Section: Reaction Solvents As Precursors For the Installation Of Key mentioning
confidence: 99%
“…[15][16][17][18] With am acrocycle as hemilabile ligand, dissociation of the chelate reveals ar eceptor for cation binding.W ith iridium pincer-crown ether complexes,cations in solution can adjust the extent of acetonitrile binding and the rate of H 2 activation. [15][16][17][18] With am acrocycle as hemilabile ligand, dissociation of the chelate reveals ar eceptor for cation binding.W ith iridium pincer-crown ether complexes,cations in solution can adjust the extent of acetonitrile binding and the rate of H 2 activation.…”
mentioning
confidence: 99%
“…Considering the lack of methods for controlling substrate binding in small organometallic catalysts,w eh ave initiated ap rogram to develop ligands with ion-tunable hemilability. [15][16][17][18] With am acrocycle as hemilabile ligand, dissociation of the chelate reveals ar eceptor for cation binding.W ith iridium pincer-crown ether complexes,cations in solution can adjust the extent of acetonitrile binding and the rate of H 2 activation. [15] Only degenerate H/D exchange was observed, rather than productive catalysis,w ith mechanistic studies suggesting at unable continuum between two different activity states.…”
mentioning
confidence: 99%